Geologi dan Potensi Batubara di Daerah Bonggo dan Sekitarnya Kabupaten Jayapura, Propinsi Papua - Marcelino N. Yonas (PROMINE, 2016)
Geographically, the study area is in the region and surrounding Bonggo, Jayapura Regency. Now adays, the energy needs requires a continuous exploration in energy commodities (oil and coal).Geologically, Jayapura Residence has considerable potential for coal commodity. The research itselfis located at coordinates 139025'51 "- 139039'37" BT and 2038'20 "- 2027'46" LS. The method used inthis research are geological mapping, SRTM image interpretation and analysis of the gravity anomaly.From the results of research have encountered the presence of local coal on the river wiruway but hasuntapped potential to be mined economically. From the analysis of satellite imagery and SRTM dataprocessing gravity so, alleged anomalies while the potential presence of a carrier lithology of coal isrelatively in eastern and widespread to the north as indicated by the value anomaly contour growingeastward. This is supported by existing of coal deposits in the east outside the study area.